High-resolution MCP-TimePix3 imaging/timing detector for antimatter physics. (1st November 2022) - Glöggler, L; Caravita, R; Auzins, M; Bergmann, B; Brusa, R S; Burian, P; Camper, A; Castelli, F; Cheinet, P; Ciuryło, R; Comparat, D; Consolati, G; et al.
Abstract: We present a hybrid imaging/timing detector for force sensitive inertial measurements designed for measurements on positronium, the metastable bound state of an electron and a positron, but also suitable for applications involving other low intensity, low energy beams of neutral (antimatter)-atoms, such as antihydrogen. The performance of the prototype detector was evaluated with a tunable low energy positron beam, resulting in a spatial resolution of ≈ 12 mm, a detection efficiency of up to 40% and a time-resolution in the order of tens of ns.